Hepatic myelolipoma in two Goeldi's monkeys from South America held captive. Issue 4 (8th July 2016) - Martins, Mariana Castilho; Rahal, Sheila Canevese; Mamprim, Maria Jaqueline; Teixeira, Rodrigo Hidalgo Friciello; Teixeira, Carlos Roberto; Sequeira, Júlio Lopes; Nóbrega, Juliano
Abstract: Two cases of hepatic myelolipoma in Goeldi's monkeys from South America are described. One was a female evaluated due progressive abdominal distension. Ultrasound and computed tomography detected hepatic mass. Partial hepatectomy was performed, but the monkey died after surgery. Case 2 was a male that died suddenly, showing non‐specific clinical signs.